Research Progress on Intracranial Lymphatic Circulation and Its Involvement in Disorders - Chen, Fan; Xie, Xuan; Wang, Liang (Frontiers in Neurology, 2022)
The lymphatic system is an important part of the circulatory system, as an auxiliary system of the vein, which has the functions of immune defense, maintaining the stability of the internal environment, and regulating the pressure of the tissue. It has long been thought that there are no typical lymphatic vessels consisting of endothelial cells in the central nervous system (CNS). In recent years, studies have confirmed the presence of lymphatic vessels lined with endothelial cells in the meninges. The periventricular meninges of the CNS host different populations of immune cells that affect the immune response associated with the CNS, and the continuous drainage of interstitial and cerebrospinal fluid produced in the CNS also proceeds mainly by the lymphatic system. This fluid process mobilizes to a large extent the transfer of antigens produced by the CNS to the meningeal immune cells and subsequently to the peripheral immune system through the lymphatic network, with clinically important implications for infectious diseases, autoimmunity, and tumor immunology. In our review, we discuss recent research advances in intracranial lymphatic circulation and the pathogenesis of its associated diseases, especially the discovery of meningeal lymphatic vessels, which has led to new therapeutic targets for the treatment of diseases associated with the intracranial lymphatic system.